Prediction of CO2 gas permeability behavior of ionic liquid–polymer membranes (ILPM) - Mannan, H.A. (John Wiley and Sons Inc., 2017)
Predicting the gas permeability of ionic liquid-polymeric membranes (ILPM) is of great importance for the design of efficient gas separation membrane materials. The available models for the prediction of CO2 gas permeability through ionic liquid-polymeric membranes were analyzed using the literature data. Maxwell model was selected for modification due to relatively accurate prediction capability. The Maxwell model was modified for ionic liquid-polymeric membranes by incorporating model parameter k for the effectiveness of volume fraction of dispersed phase. The established methodology was tested for different ionic liquid-polymeric membrane systems for validation. A satisfactory agreement was observed for predicted and experimental permeability by using the current approach. This method can be used for the prediction of CO2 gas permeability through ionic liquid-polymeric membranes. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44761. © 2017 Wiley Periodicals, Inc.